Matki odchodzą — wariacje 2009 - Czyżak, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
This article proposes some considerations on a particular variation of the elegiac mood represented by and manifested in lyrical farewells of departing mothers. A review of the variants commences with an analysis of a particularly important work by Tadeusz Różewicz written at the beginning of this century — Matka odchodzi. The book was, at the time, a particular reference point for the following poetic volumes in which the theme of the death of the poet’s mother was paramount and significant. The article also focuses on volumes of poems, written by poets that belonged to different generations but shared the same date of publication, i.e. the year 2009. Both clear similarities and marked differences in the actual commitment in carrying out the theme and in creating the profiles of mothers that have passed away are to be found in the works of Piotr Sommer (Dni i noce), Jan Polkowski (Cantus) and Eugeniusz Tkaczyszyn-Dycki (Piosenka o zależnościach i uzależnieniach).